Evaluating the Effectiveness of Digital Inclusion at Private Educational Schools in Gaza Strip - M I Awad, Mohammed; O Al Majdalawi, Mahmoud; M Salama, Aladdin (International Journal of Computer (IJC), 2018)
The research aims to evaluate the process of digital inclusion and the usage of digital tools in the educational process at private schools in Gaza Strip - Palestine. Education is the beacon of knowledge and development that is accompanied by developmental processes aimed at rising and improving the quality of service through the use of digital tools in all aspects of the educational and administrative processes within a school. In this study, the research team sought to know the tools used in the process of digital integration, and the challenges and problems faced by teachers while using digital tools, in addition to providing recommendations to help solve or mitigate problems. The descriptive analytical method is adopted to carry out the research. The results of the study showed weakness in the effectiveness of the digital inclusion process and the use of digital tools in the educational process in private schools. Furthermore, recommendations to the schools’ administrations, teachers and the Ministry of Education are stated in order to alleviate the problems and challenges of using digital tools.